Lumbar stenosis: clinical case - Sá,Pedro (2014)
Lumbar stenosis is an increasingly common pathological condition that is becoming more frequent with increasing mean life expectancy, with high costs for society. It has many causes, among which degenerative, neoplastic and traumatic causes stand out. Most of the patients respond well to conservative therapy. Surgical treatment is reserved for patients who present symptoms after implementation of conservative measures. Here, a case of severe stenosis of the lumbar spine at several levels, in a female patient with pathological and surgical antecedents in the lumbar spine, is presented. The patient underwent two different decompression techniques within the same operation.